Characterization of the quality of imbibed soybean at an early stage of pre-germination for the development of a new protein food item. Issue 1 (2nd January 2014) - Tamura, Tomoko; Kamei, Asuka; Ueda, Reiko; Arai, Soichi; Mura, Kiyoshi
Abstract: This was a pilot study carried out to develop a new protein food item from imbibed soybean before germination. It identified the significance of a short stage after imbibition and before germination, and that vitamin C production was activated in as little as 16 h from the start of imbibition, without any influence on the soy protein quality or sensory acceptability, while longer imbibition caused the imbibed soybean to activate its phytophysiological metabolism for germination. DNA microarray analysis indicated that the genes for carbohydrate metabolism were up-regulated prior to 16 h, and that the expression rates of genes responsible for environmental factors were down-regulated. Thereafter, the expression rates of the genes associated with lipid metabolism and secondary metabolite production were changed. This information should contribute to a better understanding of how to develop a new soy protein item in pre-germination before active physiological processes begin.